Véronique Lane. French Genealogy of the Beat Generation: Burroughs, Ginsberg and Kerouac’s Appropriations of Modern Literature, from Rimbaud to Michaux. Bloomsbury, 2017. - Susan Pinette (Studies in 20th & 21st Century Literature, 2018)
Review of Véronique Lane. French Genealogy of the Beat Generation: Burroughs, Ginsberg and Kerouac’s Appropriations of Modern Literature, from Rimbaud to Michaux. Bloomsbury, 2017.
Keywords: Kerouac; Beat Generation; French Modernism